Female career interruption and social integration: An interaction between human capital and new media use - Li, Chunyan; Liu, Yongjin; Li, Weiming (Frontiers in Psychology, 2022)
Promoting the social integration of various groups provides a significant guarantee for China to achieve high-quality development. However, female workers, as the main force of the service industry, had suffered a greater occupational impact due to COVID-19 and loosened China’s fertility policy in 2021. After female career interruption, the change in women’s social roles and networks has aroused concern about their social integration. However, limited attention had been paid to female career interruption in existing studies about social integration. Therefore, this study developed a theoretical model to explore the relationship between female career interruption and social integration. An empirical test using data from the fourth Chinese Women’s Social Status Survey of Hainan Province was applied to evaluate the hypotheses. The results indicate that there is a significantly negative correlation between female career interruption and social integration. And there is a difference among female career interrupters with different quantiles of social integration. Furthermore, the impact of human capital on the link between female career interruption and social integration depended on the type of new media use. When female career interrupters who use strong learning-oriented new media (such as learning about news, working/business, studying online, and investing/financial management) encounter human capital, the relationship between female career interruption and social integration is minimal. In contrast, this relationship is enhanced when female career interrupters who use strong amusing-oriented new media (such as online consumption, chatting, entertainment, and games) are confronted with human capital. Meanwhile, the results of quantile regression show that the secondary moderating effect of learning-oriented new media use gradually weakens with the rise of the quantile of female social integration. And so does amusing-oriented new media use. However, a moderating effect of human capital alone is not found.